Presenting Without Pandering - Self-Marketing for Creatives A Psychological Guide - Gause, Alina (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
You practice a creative profession in performing arts or other genres and want to successfully promote yourself and do so sustainably? This book helps you to take a holistic approach that combines a focus on your personality as an artist with the special laws of the artist's profession and artistic markets:First, get to know your personal attitude toward self-marketing and develop a basic mindset. Then find your very own mode of action through initial concrete activities.Finally, benefit from numerous concrete tips and practical exercises (e.g. for preparing photo sessions, designing a profile in the social networks or contract negotiations, and much more). This book is a translation of the original German 1st edition Anbieten ohne Anbiedern - Selbstmarketing für Kreative by Alina Gause, published by Springer-Verlag GmbH Germany, part of Springer Nature in 2021. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The Author: Alina Gause has known the artistic profession for over thirty years as an actress and singer. Alongside this work, she completed a degree in psychology and has been advising and managing artists, artistic teams and institutions of all genres since 2009. Anbieten ohne Anbiedern is her third book about artists.
Step 1 Find the right attitude -- Step 2 Get into action -- Step 3 Be visible.
Keywords: Counseling; Vocational guidance; Psychology, Industrial; Counseling Psychology; Career Counseling; Work and Organizational Psychology